The Influence Of Digital Literacy, Interactive Learning Content And Technology Accessibility On Student Digital Engagement In Higher Education - Tyahya Whisnu Hendratni; Cindy Sandra Lumingkewas; Sabalius Uhai; Agus Rofi’i; Iwan Henri Kusnadi; Joko Ariawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The proposed research aims to explore the effects of Digital Literacy, Interactive Learning Content, and Technology Accessibility on Student Digital Engagement in tertiary level education. For this study, a quantitative approach using a survey was employed to gather data. Questionnaires were handed out to 200 currently enrolled students in both public and private universities who were chosen through purposive sampling. Respondents were expected to be students that digitally learn or have experience of hybrid classes and are regularly using online learning platforms. Data were analyzed using multiple linear regression. The study found that Digital Literacy, Interactive Learning Content, and Technology Accessibility, both individually and collectively, are significantly and positively related to Student Digital Engagement. The results, therefore, reveal the ways to improve students’ digital involvement, including improving students’ digital skills, designing interesting learning materials, and providing better access to educational technologies. One of the main ways this effort has been beneficial, according to the paper, is by shedding light on how inclusive and successful digital higher education is actually constructed and why it matters.